Fermentation process optimization and flavor composition analysis of plum peppermint wine - GUO Ming-yi; DENG Yan; DU Qian-hong; WU Hua-chang (Shipin yu jixie, 2023)
Objective: In order to develop and enrich fruit wine categories and diversify sensory levels, plum and peppermint were chosen out as the main materials for fermenting a compound fruit wine. Methods: Single factor test and response surface test were used to analyze the effects of mint addition amount, initial sugar degree, initial pH value and fermentation temperature on the alcohol and quality of plum peppermint wine. The fermentation process was optimized, and its sensory was analyzed. Moreover, the sensory, physical and chemical indexes and volatile components were detected. Results: The optimum fermentation conditions were as follows: peppermint content 18%, initial sugar concentration 24%, initial pH 3.9, fermented at 21 ℃. Under the control of these conditions, the alcohol content, sensory score, total sugar, total acid and dry extract content was 10.8%, 84, 3.6 g/L, 5.15 g/L and 24.6 g/L, respectively. A total of 16 kinds of flavor components were detected based on SPME-GC-MS, accounting for 81.48% of the total volatile components. The main aromatic compounds were (+) -dihydrocarvone, which had cool aroma and the flavor of orchids. Conclusion: The plum peppermint wine produced by the optimization process meets the standard requirements of fruit wine.